The direct employment effects of new businesses in Germany revisited: an empirical investigation for 1976 - 2004 - Yvonne Schindele; Antje Weyh (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
Based on an improved and extended database, the Establishment History Panel, we extend the analysis of Fritsch & Weyh (2006) by investigating the development of employment in German start-up co-horts for the period 1976 to 2004. We confirm the typical pattern of an initial increasing and then soon decreasing number of employees in start-up cohorts. Furthermore, we provide some of the first evidence for the liability of aging phenomena in Germany. Older firms face a relatively high risk of failure. Although only the largest 25% of the surviving entries grow in terms of employment, after 25 years the number of employees in these relatively large businesses strongly declines.
Keywords: D21; L10; L26; L29; M13; 330; Employment change; new firms; start-up cohorts; liability of aging; Unternehmensgründung; Unternehmensentwicklung; Beschäftigungseffekt; Deutschland